An Analysis of the Illocutionary Acts on Donald Trump's Presidential Candidacy Speech - Desinta larasati; Arjulayana - Arjulayana; Cut Novita Srikandi (Universitas Muhammadiyah Tangerang, 2020)
ABSTRACTLearning language will also relate to speech act. When a speaker produce an utterance as well as utilize it to perform an action, it means that the speaker practices speech acts. In another hand, speech acts can be defined as an utterance used by speaker to perform an action. Speech acts are divided into three such as locutionary act, illocutionary act, and perlocutionary act. One of them is illocutionary act. The illocutionary act refers to what someone does in saying something. In this act, illocutionary force is the speaker’s intent addressed to hearer. This research is aimed to find the types of illocutionary acts and identifying about how utterances in the Donald Trump’s speeches are able to be included into certain type of illocutionary acts be based on Searle’s theory. This research is designed in descriptive qualitative. The data is collected by documentation. The primary data are taken from two transcripts of Donald Trump’s presidential candidacy speeches. While the secondary data are related theories obtained from literary books and journals. The procedure of analyzing the data starts by finding out the types of illocutionary acts in the Donald Trump’s presidential candidacy speeches by using the illocutionary acts’ classifications proposed by Searle (1969). After that, the researcher also identifies about the different frequency of illocutionary acts appearances and the dominant illoctionary acts appeared in the Donald Trump’s presidential candidacy speeches. The finding shows that the type of illocutionary acts found in the Donald Trump’s speeches were assertive, commissive, expressive, and directive. Eventhough the types of illocutionary acts found in Donald Trump’s speeches were exactly the same, but they were different in the frequency of appearance. Donald Trump produced mostly assertive type of illocutionary acts and also asserting category of illocutionary type in both of the speeches. Moreover, some utterances are included into assertive type of illocutionary acts due to the fact that they have a suitability with the explanation of assertive type of illocutionary acts proposed by Searle.Keywords: Illocutionary Acts, Speech Acts, Presidential Candidacy Speeches.